Neurons in the Nonhuman Primate Amygdala and Dorsal Anterior Cingulate Cortex Signal Aversive Memory Formation under Sedation. (8th March 2021) - Samuel, Nir; Kahana, Eilat; Taub, Aryeh; Reitich-Stolero, Tamar; Paz, Rony; Raz, Aeyal
Abstract : Background: Anesthetics aim to prevent memory of unpleasant experiences. The amygdala and dorsal anterior cingulate cortex participate in forging emotional and valence-driven memory formation. It was hypothesized that this circuitry maintains its role under sedation. Methods: Two nonhuman primates underwent aversive tone–odor conditioning under sedative states induced by ketamine or midazolam (1 to 8 and 0.1 to 0.8 mg/kg, respectively). The primary outcome was behavioral and neural evidence suggesting memory formation. This study simultaneously measured conditioned inspiratory changes and changes in firing rate of single neurons in the amygdala and the dorsal anterior cingulate cortex in response to an expected aversive olfactory stimulus appearing during acquisition and tested their retention after recovery. Results: Aversive memory formation occurred in 26 of 59 sessions under anesthetics (16 of 29 and 10 of 30, 5 of 30 and 21 of 29 for midazolam and ketamine at low and high doses, respectively). Single-neuron responses in the amygdala and dorsal anterior cingulate cortex were positively correlated between acquisition and retention (amygdala, n = 101, r = 0.51, P < 0.001; dorsal anterior cingulate cortex, n = 121, r = 0.32, P < 0.001). Neural responses during acquisition under anesthetics were stronger in sessions exhibiting memory formation than those that did not (amygdala median response ratio, 0.52 versus 0.33, n = 101, P = 0.021; dorsal anterior cingulate cortex median response ratio, 0.48 versus 0.32, n = 121, P = 0.012). The change in firing rate of amygdala neurons during acquisition was correlated with the size of stimuli-conditioned inspiratory response during retention (n = 101, r = 0.22 P = 0.026). Thus, amygdala and dorsal anterior cingulate cortex responses during acquisition under anesthetics predicted retention. Respiratory unconditioned responses to the aversive odor anesthetics did not differ from saline controls. Conclusions: These results suggest that the amygdala–dorsal anterior cingulate cortex circuit maintains its role in acquisition and maintenance of aversive memories in nonhuman primates under sedation with ketamine and midazolam and that the stimulus valence is sufficient to drive memory formation. Abstract : In nonhuman primates, aversive memory formation occurs under midazolam and ketamine anesthesia. The firing rate of neurons in the amygdala and the dorsal cingulate cortex during memory acquisition under anesthetics predicts the memory retention response after anesthesia. These observations suggest that implicit memory formation under anesthesia follows similar rules and engages the same structures and mechanisms as in the awake state.